Socialization on Building Professionalism through Service Excellence: A Provision for Success in the World of Work - Devi Marlita; Sri Handayani; Indriyati; Lis Lesmini; Erny Sulistyaningsih (Siber Nusantara of Community Service Review, 2025)
This Community Service Activity (PKM) was conducted offline on March 5, 2026, at SMKN 8 Jakarta to enhance students’ understanding of the importance of competency development and readiness to enter the workforce. The activity was attended by 37 students who actively participated throughout the session. The implementation methods included material presentation, interactive discussions, and a question-and-answer session between the speakers and participants. The materials covered an introduction to the world of work, the development of soft skills and hard skills, and strategies for early career preparation. During the activity, participants demonstrated high enthusiasm, as reflected in their active involvement in discussions and the questions raised regarding workplace challenges and self-development. The results of the activity indicate an improvement in students’ understanding of the importance of career planning, increased self-confidence, and stronger motivation to continuously develop competencies in line with industry demands. In addition, the activity provided a platform for students to express the challenges they face and obtain direct solutions from the speakers. Therefore, this PKM activity is expected to contribute positively to preparing a competent, adaptive, and competitive young generation in the workforce.